PENENTUAN NILAI KOEFISIEN SERAPAN BAHAN DAN DOSIS RADIASI PADA VARIASI KOMBINASI KAYU DAN ALUMINIUM - Andri Yanyah; Heri Sutanto (Youngster Physics Journal, 2015)
In testing the material absorption coefficient of lead Pb, teak, ironwood and aluminum: The X-ray unit is set at a fixed voltage, current and time on the conditions of 81 kV and 32 mAs. The distance between the tube to the object as far as 100 cm, Multi Purpose Detector (MPD) is placed under the object, size of field radiation is 5 cm x 5 cm, the center beam is placed right in the middle of the object, then do exposure for each thickness of lead Pb, teak, ironwood, aluminum, combination of aluminum and teak, then combination of ironwood with aluminum performed in sequence according to the variations thickness of the material.The results of material coefficient absorption testing for teak wood, ironwood and aluminum, showed the value of the absorption coefficient (μ) for teak 0,023 /mm, ironwood 0,031 /mm and aluminum 0,102 /mm. Equality results between teak, ironwood and aluminum to the lead Pb at thickness of 2 mm, teak wood 472 mm, ironwood 350 mm and for aluminum 102 mm. In thickness combination of 30 mm teak and 30 mm aluminum, absorbed dose that passes material is 0,042 mGy. For the thickness combination of 30 mm ironwood with 30 mm aluminum, the absorbed dose that passes through the material is 0,035 mGy. To be equal with the lead Pb at 1,3 mm thickness, each material has very far equality value due to the thickness of 1,3 mm Pb can absorb dose that passes through the material equal with 0,001 mGy. Keywords: X-ray mobile, Multi Purpose Detector (MPD), Absorption Coefficient (), Pb, Jati, Ulin, Aluminium